Concentration of Heavy Metals of Pb, Cu, and Zn in Avicennia marina in the Coastal Waters of Batam Riau Islands Province - Harry Leonardo Barutu; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A study on the accumulation of heavy metal by mangrove in Batam coastal waters was conducted in February 2014 by analyzing the concentration of heavy metals of Pb, Cu, and Zn in the roots, trunk, leaves and fruit of A. marina growing in the industrial and non- industrial areas. Survey method was applied at 4 stations with 3 replications each. The results showed that the highest concentration of Pb in A. marina was found in the fruit (4.47 μg/g) and the lowest was in the trunk (3.96 μg/g). The highest concentration of Cu in the roots of A. marina was 8.47 μg/g and lowest was in the leaves 7.88 μg/g. While the highest Zn concentrations in A. marina was identified in the trunk (36.69 μg/g) and the lowest was in the roots (34.99 μg/g). The concentrations of Pb, Cu and Zn in non-industrial region ware higher than that in the industrial area, but statistically they were not significantly different (p > 0.05) for Pb and Cu, it was significantly different (p < 0.05) for Zn.Keywords : Avicennia marina, heavy metals, shipbuilding industry, Batam Island